Literacy practices of an English language teacher in two pre-university high-stakes examination-oriented settings / Mojtaba Rajabi - Rajabi, Mojtaba (2015)
The main objective of the study is to provide a critical understanding of literacy practices in pre-university high-stakes examination-oriented English language education settings in Gonbad Qabus City in Northern Iran. In this context, high-stakes examinations refer to two national examinations namely, the Konkoor Examination and National High School Graduation examination, which have important consequences for students' entry to university. Specifically, this study addresses the macro level literacy practices observed in the core curriculum and the micro level teaching language literacy by the same teacher in two schooling systems with the same high-stakes examinations. Theoretically, the study is grounded in Street’s socially situated/ideological model of literacy and Foucault’s social theory of power. The present study employs a qualitative research methodology. It specifically focuses on a case of an Iranian teacher who implements teaching English language in two schooling systems, namely in a mainstream state-run and in a privately-run schooling system. This case study analyzes data in the form of documents, classroom audiotaped observations, field notes and teacher and students individual and focus interviews. Thematic Grouping and Critical Discourse Analysis are two main data analysis procedures. The analysis of the data revealed discursivities, namely a degree of alignments, situatedness, tensions and paradoxes among macro-level literacy practices. Furthermore, there was also a sharp contrast in implementing teaching of English language literacy by the same teacher in the two settings. Specifically, in the mainstream state-run classroom, the teacher neglected parts of curriculum which were not relevant to the examination and resisted critical engagement with the content of the lesson. In the private school, there was more discursive latitude in which the same teacher, although still examination-oriented, explored critical questions and literacies through a shunting back and forth movement between banking and critical pedagogy.